The global dispersion of innovative activities: The case of Finnish multinationals - Christopher Palmberg; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2004)
The internationalisation of R&D of multinational firms is an important ingredient in the ongoing trend towards globalisation. Previous research on Finnish multinationals has mainly relied on R&D expenditure data. In this paper we provide new insights into how the internationalisation of R&D of these Finnish multinationals is also reflected in their innovative output as measured by patenting. The results indicate that inventor teams have grown in size over time, especially through the entry of US, German, Swedish and UK inventors. Contrary to what the extant literature predicts, the share of patents with foreign inventors is lower for Finnish multinationals when com-pared with multinationals from other industrialised countries. However, foreign patents of Finnish multinationals score higher in terms of originality and point to the domina-tion of home-base-augmenting R&D strategies over home-base-exploiting ones. – internationalisation ; Finnish multinationals ; inventors ; patenting – – Monikansallisten yritysten t&k-toimintojen kansainvälistyminen on oleellinen osa menneillään olevaa globalisoitumiskehitystä. Aikaisemmissa suomalais-ten monikansallisten yritysten innovaatiotoiminnan kansainvälistymistä käsitelleissä tutkimuksissa on aihetta analysoitu pääosin t&k-menojen avulla. Tässä tutkimuksessa hyödynnetään sitä vastoin patenttitietoja, jotka kuvaavat paremmin innovaatiotoiminnan tuloksellisuutta. Suomalaisten monikansallisten yritysten innovaatiotoiminta on paten-toinnin valossa kansainvälistynyt viime vuosikymmenten aikana, etenkin keksijöiden määrä USA:sta, Saksasta, Ruotsista ja Iso-Britanniasta on lisääntynyt. Ulkomaisten yk-siköiden osuus patentoinnissa on kuitenkin edelleen alhaisempi kuin monissa muissa teollisuusmaissa. Patenttien teknologista merkitsevyyttä kuvaava tunnusluku oli sen sijaan keskimäärin korkeampi yritysten ulkomaisten t&k-yksiköiden patenteissa koti-maisten t&k-yksiköiden patentteihin verrattuna. Tämä viittaa siihen, että ulkomaisten t&k-yksiköiden toiminta on edesauttanut suomalaisten monikansallisten yritysten tekno-logisen perustan vahvistumista. – kansainvälistyminen ; monikansalliset yritykset ; patentointi ; keksijät
Keywords: 330; Innovationsdiffusion; Globalisierung; Multinationales Unternehmen; Finnland